Defect formation by order coalescence in vermicular grains during alumina phase transformation. (October 2015) - Wang, Ling; Hu, Jianfeng; Cheng, Yao; Fu, Zhengyi; Shen, Zhijian; Xiong, Yan
Graphical abstract: Abstract: Vermicular α-Al2 O3 grains obtained from γ- to α-phase transformation were investigated. X-ray diffraction patterns showed a left-shifting shoulder in all diffraction peaks of transformed α-Al2 O3 . High-resolution transmission electron microscopy results confirmed large amounts of defects inside the vermicular α-Al2 O3 single-crystal. Combined with grain-growth discontinuity, the authors proposed that the defects inside vermicular grains resulted from assembly of nanosized α-crystallites by an ordered coalescence mechanism directly after phase transformation, by which the orientation alignment was thermodynamically favored in the solid-state sintering.